2013
DOI: 10.1111/imre.12035
|View full text |Cite
|
Sign up to set email alerts
|

Global Changes and Gendered Responses: The Feminization of Migration from Georgia

Abstract: While frequently discussed, the feminization of migration remains among the least understood trends in migration literature. Existing research links feminization of migration to socioeconomic change in migrant origin countries, changes in destination-country labor markets, structural factors, and changing social attitudes. However, questions of how the feminization of migration begins and how it becomes socially institutionalized remain largely unanswered. Having experienced a recent, dramatic increase in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…6 Although labor migration from Central Asia started as almost exclusively male, the share of female migrants has rapidly grown (Khusenova 2013; Tyurukanova 2011), paralleling trends in other parts of the former Soviet Union (e.g., Hoffmann and Buckley 2013) and elsewhere in the world (Donato and Gabaccia 2015). In today’s Russia, some 40%, 17%, and 19% of registered Kyrgyz, Tajik, and Uzbek nationals, respectively, are women (FMS 2015a), and increasingly women migrate on their own rather than accompanying/following their male partners (Tyurukanova 2011).…”
Section: Migration From Central Asia To Russiamentioning
confidence: 99%
See 1 more Smart Citation
“…6 Although labor migration from Central Asia started as almost exclusively male, the share of female migrants has rapidly grown (Khusenova 2013; Tyurukanova 2011), paralleling trends in other parts of the former Soviet Union (e.g., Hoffmann and Buckley 2013) and elsewhere in the world (Donato and Gabaccia 2015). In today’s Russia, some 40%, 17%, and 19% of registered Kyrgyz, Tajik, and Uzbek nationals, respectively, are women (FMS 2015a), and increasingly women migrate on their own rather than accompanying/following their male partners (Tyurukanova 2011).…”
Section: Migration From Central Asia To Russiamentioning
confidence: 99%
“…Whereas several studies have examined the transformation of gender ideologies and relations in the southern periphery of the former Soviet Union as both a catalyst and a consequence of labor migration (e.g., Hoffmann and Buckley 2013; Reeves 2013a), the scholarship focusing on migrant women’s experience in Russia remains very limited. The few existing analyses typically note cultural and economic challenges that Central Asian migrant women face as they seek to reconcile traditional gender norms with demands and expectations in the Russian labor market (Tyurukanova 2011), challenges that are further exacerbated by entrenched gender inequalities in Russian society (e.g., Kosyakova, Kurakin, and Blossfeld 2015).…”
Section: Migration From Central Asia To Russiamentioning
confidence: 99%
“…). Lone female labor migration from Georgia is much more common than from other countries, including Mexico (Hofmann and Buckley ), probably due to the socioeconomic position of Georgian women and the growing demand for female migrant labor in the domestic and care work sectors of Western countries (Badurashvili ; Chindea et al. ; Zurabishvili and Zurabishvili ).…”
Section: Gender and Migration In The Republic Of Georgiamentioning
confidence: 99%
“…Because previous research has demonstrated that correlates of migration for men and women are often different (Hofmann and Buckley 2013), I separate male and female migrants. I also conducted multinomial logistic regression analyses, comparing the odds of going to the FSU, Greece/Turkey, or Western Europe versus going to Russia (the 'all others' destination category is eliminated).…”
Section: Reason For Migrationmentioning
confidence: 99%
“…Western Europe receives the highest proportion of college-educated migrants, and the highest proportion of migrants from urban areas. This may be related to the fact that educational exchange and au pair programmes are one of the most reliable ways of obtaining a visa to many Western European countries (Hofmann and Buckley 2013). Greece and Turkey, on the other hand, receive the least college-educated migrants.…”
Section: Financial Costsmentioning
confidence: 99%